Cu(I)-catalyzed synthesis of N-tosyl-4-iminoquinolizines. Issue 27 (1st July 2015) - Chen, Joanna L.; Namirembe, Sheila; Lauchert, Luke T.; Tsougranis, Gregory H.; Isaacs, André K.
Graphical abstract: Abstract: Pyridines were found to be a convenient nucleophile in the copper(I)-catalyzed synthesis of N -tosyl-4-iminoquinolizines from 2-pyridyl compounds. Intramolecular cyclization of an in situ generated ketenimine and a tethered pyridine, followed by a base-promoted oxidation, affords the desired products in moderate to good yields under mild reaction conditions.